Leadership Matters: Tensions in Evaluating Leadership Development. (February 2013) - Jarvis, Carol; Gulati, Anita; McCririck, Virginia; Simpson, Peter
The Problem: This article explores some of the tensions that required careful management in the design and delivery of a leadership development program. This discussion draws particularly upon a formal evaluation of two cohorts, each comprising approximately 20 senior managers working in adult social care. Complexity theory, notably Complex Responsive Processes of Relating, is used to make visible, explore and articulate the need to hold in tension apparently contradictory forces and requirements. The program was established at a critical time in the U.K. government's public services reform agenda, which was unfolding during a period of increasing resource constraint. This included a requirement upon commissioners to demonstrate impact and return on investment (ROI) in development programs. However, complexity theory explains why a direct causal relationship between inputs and outcomes is not amenable to demonstration by evaluation. The Solution: Consequently, the approach to demonstrating ROI explored the microprocesses underpinning the development of the participants' thinking and practice through formative real time and post hoc evaluation. This comprised a range of qualitative techniques: extended observations provided an "ethnographic" overview of the program; participant and stakeholder interviews gave insight into critical incidents and key learning points; and guided conversations placed greater emphasis on the everyday experience of participants in applying their learning. It is argued that such an approach to evaluation is both a research intervention and a contribution to the development process. The Stakeholders: Our article will be of particular relevance to human resource professionals, leadership development practitioners, commissioners, business schools and evaluators facing the challenge of finding meaningful measures of "ROI" for individual and organizational development.